Thymic nurse cells provide microenvironment for secondary T cell receptor α rearrangement in cortical thymocytes - Nakagawa, Yasushi (National Academy of Sciences, 2012)
Distinct subsets of thymic epithelial cells (TECs) support T-cell development and selection. Isolated TECs contain multicellular complexes that enclose many viable thymocytes. However, the functions of those TECs, termed thymic nurse cells (TNCs), are unclear and the idea that TNCs are present in vivo is questioned. Here, we show that TNCs represent a fraction of cortical (c)TECs that are defined by the expression of thymoproteasomes. Intravital imaging revealed TNCs in the thymic cortex in situ, whereas TNCs were detected neither during embryogenesis nor in the postnatal thymuses of various “positive-selector” T-cell receptor (TCR)-transgenic mice, indicating that TNCs are not essential for T-cell differentiation, including positive selection. Rather, cells within TNCs were enriched for long-lived CD4(+)CD8(+) thymocytes that underwent secondary TCR-Vα rearrangement. Thus, TNC complexes are formed in vivo by persistent cTEC–thymocyte interactions that then provide a microenvironment that optimizes T-cell selection through secondary TCR rearrangement.